Transboundary water resources for people and nature: Challenges and opportunities in the Olifants river basin - Alisher Mirzabaev; Georgina Wambui Njiraini; Gebrelibanos Gebremariam; Damien Jourdain; Emílio Magaia; Felita Julio; Gerivásia Mosse; Jo\~ao Mutondo; Eric Mungatana (University of Bonn, Center for Development Research (ZEF), 2019)
This paper proposes that transboundary water governance needs to become an essential input to sustainable governance of protected natural reserves. The paper reviews the challenges and opportunities for such governance mechanisms, and identifies the factors behind successful practices. Successful transboundary governance of water and nature requires the reduction of associated transaction costs. Firstly, water diplomacy through joint research, data collection and monitoring, capacity building, dialogues for consensus building, promoting responsible leadership and providing advisory support can help in overcoming mistrust between stakeholders and create opportunities for cooperation. Secondly, power asymmetries may hinder transboundary water governance, therefore, there is a need to involve multi-scale links across stakeholders to counter-balance local power asymmetries and engage all stakeholders in consultations and negotiations. Thirdly, transboundary water governance is critically dependent on accurate and transparent data and analysis tools for informing policy decisions. Science-policy interactions for facilitating transboundary water governance were found to be most effective when the knowledge on joint water and nature governance is coproduced in a trans-disciplinary manner, in collaboration with wide-ranging informal networks of scientists, policy makers, and civil society. Finally, transboundary water governance organizations can serve as platforms for facilitating water diplomacy, building trust and cooperation, especially when they are granted the ability to enter into binding cooperative agreements regardless of external political pressures.
Keywords: O13; Q01; Q25; Q26; Q51; Q52; Q57; 330; Transboundary water and nature governance; game theory; transaction cost; stakeholder analysis; Olifants river basin